The Effect of Online Learning on Students Learning Motivation - Sa'diyah, Halimatus; Rahma Pratiwi, Emy Yunita (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2021)
Online learning began in early March 2020. With this online learning, most parents complained when online learning began. Because many students are angry, and yell at their parents when they are told to study, even when there is a test they don't want to study at all. This study aims to determine how big the level of student learning motivation during online learning at SDN Puton, Diwek District, Jombang Regency. This study uses quantitative methods in processing the data using samples. The sample used in this study was grade 6 students, totaling 32 students. In this study using data collection techniques in the form of questionnaires and documentation. Questionnaires are aimed at students to find out about their learning motivation, and documentation aims to obtain information about student data, student learning outcomes and a brief history of the establishment of the school, the school's vision and mission, school conditions and so on. The results in this study can be concluded that there is a significant effect of online learning on the level of student motivation. Where the significant value of tcount (5% = 170.592) is greater than ttable (0.361) and at a significant level of 0.000 less than 0.05 so it can be concluded that in the alternative hypothesis research Ha is accepted and Ho is rejected. This means that there is a very large influence of online learning on learning motivation in grade 6 students at SDN Puton, seen from the calculation of the coefficient of determination of 85% of the influence. Keywords: Influence, online learning, motivation